Integrasi Nilai-Nilai Karakter dalam Kurikulum Pendidikan Agama Islam di Madrasah Ibtidaiyah - Muarifah, Muarifah; Fatimah, Meti; Subando, Joko (Lembaga Yasin AlSys, 2026)
The integration of character values into the Islamic Religious Education (PAI) curriculum in Madrasah Ibtidaiyah has become increasingly urgent as a normative, pedagogical, and sociocultural mandate for cultivating a morally upright generation amid the challenges of globalization. This article aims to provide a comprehensive analysis of the integration of character values within the PAI curriculum in Madrasah Ibtidaiyah. The discussion is based on Chapter II (literature review) of a thesis on the integration of character values in the PAI curriculum, employing a qualitative–descriptive approach through theoretical examination and relevant research. The integration of character values is understood as a systematic process that embeds religious values, honesty, discipline, responsibility, social concern, and noble character into the objectives, content, methods, and evaluation of PAI learning. The findings indicate that effective integration requires explicit curriculum planning, exemplary teacher conduct, continuous habituation, the strengthening of a religious school culture, and authentic affective evaluation. These findings affirm that character value integration in PAI is a crucial prerequisite for developing a curriculum that is both responsive to global challenges and oriented toward the formation of students’ noble character. This article is expected to provide theoretical and practical contributions to the development of the PAI curriculum in Madrasah Ibtidaiyah, particularly in designing more systematic and sustainable strategies for integrating character values.